Kompetensi Organisasi - Nursalim, M Fahri; Anshori, Mohammad Isa (CV. Lenggogeni Data Publishing, 2024)
Organizational skills play an important role in achieving business goals. Organizations with strong capabilities can adapt quickly to changes, produce high-quality products, and build a competitive advantage. This research analyzes the relationship between organizational capabilities and business success. Through a literature review and descriptive analysis, this study identifies organizational competency factors that have a significant impact on business success. The results highlight the importance of investing in employee skills development, an organizational culture that supports learning and innovation, and strategic partnerships with external stakeholders. Understanding organizational capabilities and translating them into business strategy is key to the long-term success of an organization. AbstrakKeterampilan organisasi memainkan peran penting dalam mencapai tujuan bisnis. Organisasi dengan kapabilitas yang kuat dapat beradaptasi dengan cepat terhadap perubahan, menghasilkan produk berkualitas tinggi, dan membangun keunggulan kompetitif. Penelitian ini menganalisis hubungan antara kapabilitas organisasi dan kesuksesan bisnis. Melalui tinjauan literatur dan analisis deskriptif, penelitian ini mengidentifikasi faktor-faktor kompetensi organisasi yang mempunyai dampak signifikan terhadap keberhasilan bisnis. Hasilnya menyoroti pentingnya berinvestasi dalam pengembangan keterampilan karyawan, budaya organisasi yang mendukung pembelajaran dan inovasi, dan kemitraan strategis dengan pemangku kepentingan eksternal. Memahami kapabilitas organisasi dan menerjemahkannya ke dalam strategi bisnis adalah kunci keberhasilan jangka panjang suatu organisasi.